Knowledge and attitude towards person with mental illness among community in Tanjung Sepat, Selangor - Sambanthan, Yasheni (2020)
Mental illnesses are health conditions that involve changes in emotion, thinking, behaviour or combination of these. It can affect anyone regardless of age, gender, income, social status, race, religion or background. It is important for the community to have positive attitude towards person with mental illness so that they would seek early treatment without any fear of stigma. A cross sectional study was conducted on 140 respondents recruited by using a simple random sampling method. A validated questionnaire was given to all respondents that fit the inclusion criteria. The general objective of the study was to assess the knowledge and attitude towards person with mental illness among community in Tanjung Sepat. Demographic data of the respondents was analysed by using descriptive statistic. Descriptive statistic was also used to assess the level of knowledge and level of attitude of community in Tanjung Sepat towards person with mental illness. Spearman’s correlation test was applied to determine the relationship between the knowledge and attitude towards person with mental illness. The findings revealed that majority of community in Tanjung Sepat have good knowledge on mental illness and positive attitude towards person with mental illness. In this study, there is no statistically significant association between selected socio-demographic data (gender, age and level of education) with knowledge and attitude towards person with mental illness. There is a very weak positive correlation between knowledge and attitude towards person with mental illness. The finding shows that those with good knowledge on mental illness have favourable attitude towards the person with mental illness.